Challenges in determining soil moisture and evaporation fluxes using distributed temperature sensing methods. (1st May 2020) - Lagos, Magdalena; Serna, José Luis; Muñoz, José Francisco; Suárez, Francisco
Abstract: To protect fragile groundwater-dependent environments of arid zones, it is important to monitor soil moisture and groundwater evaporation. Hence, it is important to assess new methods to quantify these environmental variables. In this work, we propose a new method to determine groundwater evaporation rates by combining the actively heated fiber-optic (AHFO) method with vadose zone modeling, assuming that the evaporation front remains at the soil surface. In our study, the AHFO method yielded estimates of the soil moisture ( θ ) profile with a spatial resolution of 6.5 mm and with an error of 0.026 m 3 m −3 . The numerical model resulted in a slightly different θ profile than that measured, where the largest differences occurred at the soil surface. Sensitivity and uncertainty analyses highlighted that a better precision is required when determining the soil hydraulic parameters. To improve the proposed method, the soil heat-vapor-water dynamics should be included and the assumption that the evaporation front remains at the soil surface must be relaxed. Additionally, if the AHFO calibration curve is enhanced, the errors of the estimated θ profile can be reduced and thus, successful estimation of the evaporation rates for a wider range of soil textures can be achieved. The spatial scales measured are an important advantage of the proposed method that should be further explored to improve the analysis presented here. Graphical abstract: Image 1 Highlights: New method to determine evaporation fluxes using soil moisture derived from DTS. The method provides better results for fine-textured soils. The method performs better when soil hydraulic properties are accurately determined. The method will perform better when soil heat-vapor-water dynamics are considered.